Elastic Kernmantle E‐Braids for High‐Impact Sports Monitoring. Issue 25 (27th June 2022) - Wang, Wei; Yu, Aifang; Wang, Yulong; Jia, Mengmeng; Guo, Pengwen; Ren, Lele; Guo, Di; Pu, Xiong; Wang, Zhong Lin; Zhai, Junyi
Abstract: The kernmantle construction, a kind of braiding structure that is characterized by the kern absorbing most of the stress and the mantle protecting the kern, is widely employed in the field of loading and rescue services, but rarely in flexible electronics. Here, a novel kernmantle electronic braid (E‐braid) for high‐impact sports monitoring, is proposed. The as‐fabricated E‐braids not only demonstrate high strength (31 Mpa), customized elasticity, and nice machine washability (>500 washes) but also exhibit excellent electrical stability (>200 000 cycles) during stretching. For demonstration, the E‐braids are mounted to different parts of the trampoline for athletes' locomotor behavior monitoring. Furthermore, the E‐braids are proved to act as multifarious intelligent sports gear or wearable equipment such as electronic jump rope and respiration monitoring belt. This study expands the kernmantle structure to soft flexible electronics and then accelerates the development of quantitative analysis in modern sports industry and athletes' healthcare. Abstract : Herein, the kernmantle structure is introduced into flexible electronics, specially, a robust and elastic kernmantle electronic braid (E‐braid) for self‐powered high‐impact sports monitoring is developed. This study introduces the new member—E‐braid for e‐textile family and then, accelerates the development of quantitative analysis in modern sports industry and athletes' healthcare.